2022
DOI: 10.1002/ejic.202200550
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Approach for Generation of Oxygen Vacancies in Trirutile MnSb2O6 and Their Impact on Photocatalytic Degradation of MO Dye

Abstract: Visible light‐driven photocatalysis has gained much attention due to its light‐harnessing characteristics and is extensively used in wastewater remediation. This paper presents a novel oxygen‐deficient manganese antimonate, MnSb2O6‐x, with a trirutile structure as an effective visible‐light‐driven photocatalyst for dye degradation. The synthesized samples were subjected to XRD, UV‐Vis DRS, SEM‐EDS, Raman, XPS, and PL analyses to study their physic chemical properties. The influence of sequential or single heat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
(71 reference statements)
0
1
0
Order By: Relevance
“…For example, Arunkumar and Naraginti [ 17 ] studied for the first time the photocatalytic activity (under visible light conditions) of CoSb 2 O 6 , CuSb 2 O 6 , NiSb 2 O 6 , and FeSb 2 O 6 for p-nitrophenol degradation. Liu et al [ 18 ] studied the photocatalytic effect of ZnSb 2 O 6 nanoparticles using the discoloration of rhodamine B and methyl orange (MO); Zhang et al [ 19 ] synthesized nanoparticles of CaSb 2 O 6 that showed high photocatalytic performance for the degradation of MO; Sunku et al [ 20 ] studied the degradation of MO by using MnSb 2 O 6 under visible light conditions; and Papi et al [ 21 ] synthesized NiSb 2 O 6 nanoparticles with high photocatalytic performance in the degradation of an aqueous solution of malachite green (MG). However, there have been few studies on trirutile-type antimonates applied in photocatalysis.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Arunkumar and Naraginti [ 17 ] studied for the first time the photocatalytic activity (under visible light conditions) of CoSb 2 O 6 , CuSb 2 O 6 , NiSb 2 O 6 , and FeSb 2 O 6 for p-nitrophenol degradation. Liu et al [ 18 ] studied the photocatalytic effect of ZnSb 2 O 6 nanoparticles using the discoloration of rhodamine B and methyl orange (MO); Zhang et al [ 19 ] synthesized nanoparticles of CaSb 2 O 6 that showed high photocatalytic performance for the degradation of MO; Sunku et al [ 20 ] studied the degradation of MO by using MnSb 2 O 6 under visible light conditions; and Papi et al [ 21 ] synthesized NiSb 2 O 6 nanoparticles with high photocatalytic performance in the degradation of an aqueous solution of malachite green (MG). However, there have been few studies on trirutile-type antimonates applied in photocatalysis.…”
Section: Introductionmentioning
confidence: 99%